School geography in the context of the occupation movements of brazilian schools - Silva, Alcinéia de Souza (Geosaberes; Vol 8 No 15 (2017): May - Aug, 2017)
This work has the ambition to methodically weave some notes on the paths and challenges of School Geography in the context of significant student movements of occupation of Brazilian schools. Represented by the struggles of redemocratization and resistance to the educational reforms in the country, the movements reveal the characteristics of a new school subject and brings reflection on the pedagogical practices developed by the school, in general and geographic education, in a particular way. On the basis of this, through a bibliographical review on this theme, as well as empirical research with the young protagonists of the movement carried out in the city of Formosa-Goiás, the objective is to highlight the role of Geography in the citizen's formation of the student from the world’s critical reading.
Keywords: Cidadania; Geografia Escolar; Ocupação de escolas.